A Comparative Study of Infertility in Crossbred Cows and Buffaloes Under Village Management - SREEMANNARAYANA, O; NARASIMHARA0, A V (The Indian Journal of Animal Reproduction, 2023)
The incidence and variation of different forms of infertility among 602 crossbred cows and 4,435 buffaloes maintained under similar rural conditions was studied. The incidence of ovarian acyclia and ovulatory aberrations among crossbreds and genital infections among buffaloes was significantly higher. Of the single disorders, P.OSt partum anoestrus and repeat breeding among crossbreds, smooth ovaries and endometritis among buffaloes occurred at a significantly higher frequency rate.